Trigger-happy or precisionist? On demand for monitoring in a noisy social dilemma game - Andreas Nicklisch; Louis G. Putterman; Christian Thöni (Brown University, Department of Economics, 2019)
Recent experimental studies question whether societies can selfgovern social dilemmas with the help of decentralized punishment opportunities. One important challenge for the mechanism is imperfect information about cooperative behavior. It has been shown that imperfect information increases misdirected punishment and thereby hampers the efficacy of the punishment mechanism. We study an environment with monitoring opportunities, in which subjects can improve the quality of their information at a cost. We find experimentally that the majority of subjects are willing to pay a modest cost to improve their information. The demand for monitoring is price sensitive, but does not systematically depend on whether other subjects are informed about the monitoring decision. Almost no subjects take up the chance to monitor partially at a lower price. Rather subjects choose to monitor either perfectly or not at all. Little punishment takes place with imperfect information. The large majority of those subjects who monitor subsequently punish non-cooperative behavior, leading to a substantial and significant improvement in efficiency.
Keywords: C92; D02; H41; 330; public goods; peer punishment; costly monitoring